Versailles, the visit - Saule, Beatrix; Corbiau, Gérard; Petitgirard, Laurent; Chateau de Versailles (Versailles, France).; Reunion des musees nationaux (France).; Montparnasse Productions (Firm).; Public Media Video (Firm).; Home Vision Entertainment (Firm). ([United States] Public Media, 2002)
Visit the world's most famous chateau in the heart of Versailles. Discover the palace, the park, and the gardens through a circut arranged chronologically and by subject matter. Certain areas generally closed to the public are shown as well.
Title from cassette label.
Music composer, Laurent Petitgiard.
VHS, Hi-fi, stereo.
Keywords: Palaces -- France; Chateau de Versailles (Versailles, France).; France -- Description and travel